PERAN KEBIJAKAN DIVIDEN MEMEDIASI LEVERAGE DAN EARNING PER SHARE TERHADAP RETURN SAHAM - Astuti, Indri Puji; Faizah, Erna Nur; Lailiyah, Elliv Hidayatul (COMPETITIVE, 2024)
This study aims to determine the dividend policy mediates leverage and earnings per share on stock returns in the LQ-45 Index Company for the 2016-2022 Period. This type of research is quantitative research using secondary data. The population in this study were LQ-45 Index Companies for the 2016-2022 Period. The sampling technique used purposive sampling so that 12 companies were obtained as samples. This study uses path analysis and sobel test with tools in the form of SPSS (Statistical Package for Social Science) computer software. The results of this study indicate that leverage has a negative effect on dividend policy, earning per share has no effect on dividend policy, leverage and earning per share have no effect on stock returns, dividend policy has no effect on stock returns, while dividend policy does not mediate leverage and earning per share on stock returns.